2020
DOI: 10.1186/s12889-020-08994-x
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a progressive resistance exercise program for industrial workers during breaks on perceived fatigue control: a cluster randomized controlled trial

Abstract: Background: There is strong evidence that physical exercise in the workplace is effective for reducing workers' musculoskeletal complaints. Studies with industrial workers and studies on progressive resistance exercises during breaks are scarce. Our aim was to evaluate the effects of a resistance exercise program on perceived fatigue control among industrial workers. Methods: 204 employees from the dairy industry were allocated to two groups, the intervention group (IG) (n = 98) and the control group (CG) (n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
0
13

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(53 citation statements)
references
References 38 publications
1
39
0
13
Order By: Relevance
“…Most other studies were carried out over a longer duration [28][29][30]39]; this study showed a decrease in complaints of general musculoskeletal fatigue over the four-week intervention. Previous research, conducted by Lee et al [50], showed a significant decrease in musculoskeletal symptoms in the neck and shoulders after self-stretching exercise for 4 weeks.…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…Most other studies were carried out over a longer duration [28][29][30]39]; this study showed a decrease in complaints of general musculoskeletal fatigue over the four-week intervention. Previous research, conducted by Lee et al [50], showed a significant decrease in musculoskeletal symptoms in the neck and shoulders after self-stretching exercise for 4 weeks.…”
Section: Discussionmentioning
confidence: 65%
“…Most studies were interested in strengthening or resistance exercises, including the study of Santos et al [28] and Andersen et al [33,34,37]; they emphasized that strengthening exercises and specific resistance training of the upper extremity can relieve musculoskeletal pain symptoms in office workers. However, this study looked at the effect of combination stretching and BG + TfH movements that can reduce musculoskeletal complaints without using assistive devices, the movements are not a high risk if you experience the wrong movements, the movements are easy and light.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, a treatment which affects the mean of an outcome variable can also be expected to affect its variance, making the assumption of homogeneity of variance realistic only under the null hypothesis. Published evidence on this assumption is scarce as homogeneity is routinely assumed in data analysis and rarely tested and reported explicitly, but there is some evidence for heterogeneity in CRTs (for some examples, see Roberts & Roberts, 2005; ; Cheyne et al., 2008; Adachi et al., 2013; Santos et al., 2020), and even more so in clinical psychology (Grissom, 2000). Finally, with respect to costs, the study costs for sampling, treating, and measuring clusters and persons in one treatment arm may be different from those in the other arm.…”
Section: Introductionmentioning
confidence: 99%